Anti-adherence capacity of phytosphingosine on titanium surfaces - Liinoja, Enni; Areid, Nagat; Närvä, Elisa; Bikker, Floris J.; Loimaranta, Vuokko; Närhi, Timo O. (SAGE PUBLICATIONS LTD, 2025)
Firm soft tissue attachment on oral implant components together with good bacterial control are important prerequisites for uneventful implant healing. TiO2 coatings have been shown to enhance human gingival fibroblast attachment, but the coating does not have antimicrobial properties. Phytosphingosine (PHS) is known to have antifouling properties against the cariogenic bacterium Streptococcus mutans (S. mutans) which is also among the first colonizers on implant surfaces. This makes PHS an interesting agent to prevent microbial adhesion on dental implant surfaces. The aim of this study was to examine the impact of PHS on S. mutans and human gingival fibroblast adhesion on titanium surfaces with or without TiO2 -coating. Titanium discs (n = 99, diameter 14 mm, thickness 1 mm) were fabricated for the study. The discs were divided into four groups: (1) non-coated discs (NC), (2) titanium discs with hydrothermally induced TiO2 coatings (HT), (3) NC discs treated with PHS solution and (4) HT discs treated with PHS solution. Hydrophilicity of the discs was evaluated by water contact angle measurement. S. mutans was added on HT and NC discs with or without PHS treatment for 30 minutes and the number of attached bacteria was estimated by plate counting method. For fibroblast experiment, the cells were plated on the discs and the number of adhered fibroblasts was determined at three time points (1, 3, 6 h). Additionally, confocal microscope images were obtained to examine fibroblast and S. mutans adhesion and to evaluate cell spreading. PHS treatment significantly decreased the hydrophilicity of HT and NC titanium surfaces (p < .001). S. mutans adhesion was significantly reduced after PHS treatment on both NC (p < .001) and HT surfaces (p < .001). Fibroblast adhesion was significantly reduced in HT group at 1 and 3h time points (p < .001), situation leveling out by the 6th hour. PHS reduced the number of adhered fibroblasts to the surface at incubation times of 1 hours (p = .0011) and 3 hours (p = .0194). At the 6 hour time point the number of adhered cells was no longer reduced, but still a reduction in cell spreading on the surface was observed (p < .05). The adhesion differences were present only in HT group. The PHS treatment reduced adherence of S. mutans and fibroblasts on TiO2 coated titanium, which may result from reduced hydrophilicity of the surfaces. The dual approach of PHS treatment and TiO2 coating could provide microbial antifouling properties of dental implants but may also affect fibroblast adhesion.